Islamic Religious Education Teachers' Strategies in Addressing the Development of Precocious Adolescents at SMP Negeri 1 Karang Baru, Aceh Tamiang - Malawati Malawati; Mulyadi Mulyadi; Lathifah Hanum (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
Research Objectives: 1). To analyze the strategies implemented by Islamic Religious Education teachers in addressing the development of puberty adolescents at SMP Negeri 1 Karang Baru. 2). To analyze the effectiveness of Islamic Religious Education teachers' strategies in shaping the character and spirituality of students during puberty at SMP Negeri 1 Karang Baru. 3). To identify supporting and inhibiting factors in the implementation of strategies for fostering puberty adolescents implemented by Islamic Religious Education teachers at SMP Negeri 1 Karang Baru. The research method used was qualitative with a phenomenological approach. Data collection was conducted through observation, interviews, and documentation. Data analysis techniques were carried out through data reduction, data presentation, and drawing conclusions. The results of the study are: 1). The strategy of Islamic Religious Education teachers at SMP Negeri 1 Karang Baru in addressing adolescent development during puberty is carried out by linking Islamic teachings to the reality of puberty, providing role models, and providing spiritual-emotional guidance. Teachers not only deliver material, but also guide students to understand the puberty phase as a moral and spiritual responsibility. 2). The strategy of Islamic Religious Education teachers in fostering character and spirituality of students during puberty at SMP Negeri 1 Karang Baru has proven effective. The strategy of Islamic Religious Education teachers is able to produce real changes in students at SMP Negeri 1 Karang Baru, both in the form of behavioral improvements and increased understanding of religious values. 3). Support from the school and parents is a very significant strengthening factor in creating a religious and conducive educational environment for the spiritual development of students at SMP Negeri 1 Karang Baru